Hubungan Asupan Zat Gizi Makro dengan Status Gizi Mahasiswi Program Studi S1 Gizi Unesa - Aisyah Aisyah (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
The majority of students tend to have irregular eating patterns and often consume unhealthy foods, resulting in nutritional problems such as malnutrition or overnutrition. Malnutrition makes the body more susceptible to infectious diseases, while overnutrition makes the body more susceptible to degenerative diseases. Nutritional status is basically determined by the amount of food consumed and how that food is processed in the body. This study aims to investigate the relationship between macronutrient intake and the nutritional status of female students in the Nutrition Study Program at Unesa. This study is a quantitative study with a cross-sectional design. The respondents in this study were female students in the Nutrition Study Program at Unesa, namely the 2021, 2022, and 2023 cohorts, totaling 247 students. Nutritional status data were obtained from weight and height measurements, while macronutrient intake data were obtained from food consumption measurements using a 3x24-hour food record form. Data analysis in this study used the chi-square test. The results of the chi-square test showed that there was no relationship between carbohydrate intake, fat intake, and protein intake with the nutritional status of female students in the Nutrition Study Program at Unesa.